A Multiplex One‐Step RT‐qPCR Protocol to Detect SARS‐CoV‐2 in NP/OP Swabs and Saliva. Issue 5 (18th May 2021) - Bland, Joshua; Kavanaugh, Ashley; Hong, Lenny K.; Perez, Omar; Kadkol, Shrihari S.
Abstract: Since December 2019, SARS‐CoV‐2 has spread extensively throughout the world, with more than 117 million reported cases and 2.6 million deaths (Johns Hopkins coronavirus resource center, https://coronavirus.jhu.edu/map.html ). Detecting the virus is the first step in diagnosing the infection, followed by quarantine to prevent transmission. Nasopharyngeal/oropharyngeal swabs (NP/OP) and saliva are two specimen types that are most often analyzed to detect SARS‐CoV‐2 by molecular tests that detect viral RNA or by antigen/antibody tests that detect viral proteins and/or the host immune response against the virus. Compared to antigen/antibody tests, molecular tests are highly sensitive and specific for detecting the virus. A significant drawback is that specimen collection requirements are specific to each test and cannot be interchanged with another test. Some tests are qualified to be used on NP swabs or saliva, but not both specimen types. Even with NP swabs, a test may be qualified to detect the virus only with swabs collected in viral transport medium (VTM) but not in other media. These restrictive pre‐analytic steps are disadvantageous in that a lab would have to develop and validate different tests for SARS‐CoV‐2 depending on the specimen type and collection media, with added setup cost, infrastructure, and training requirements. To overcome these problems, we developed and validated a cost‐effective multiplex reverse‐transcription real‐time PCR assay that can be used to detect SARS‐CoV‐2 in different specimen types. The assay is highly sensitive and specific, can be used to detect the virus in saliva as well as NP swabs collected in different media such as VTM, saline, and commercial preservative fluid, and serves as one test for all applications. The protocol also describes an optimal laboratory setup and unidirectional workflow for detecting SARS‐CoV‐2 by RT‐qPCR. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Manual viral nucleic acid extraction from NP/OP swabs collected in different media, and from saliva Alternate Protocol 1 : Low‐throughput automated extraction on the Qiagen EZ1 Advanced XL machine (1‐14 samples) Alternate Protocol 2 : High‐throughput automated extraction on the Kingfisher Flex machine (1‐96 samples) Basic Protocol 2 : Multiplex RT‐qPCR protocol to detect SARS‐CoV‐2 Alternate Protocol 3 : Multiplex one‐step RT‐qPCR protocol to detect SARS‐CoV‐2 with S and E gene probes labeled with the same fluorochrome